Pengaruh Literasi Digital dan Tingkat Pendidikan terhadap Partisipasi Politik Generasi Milenial Kota Bekasi - Mohammad, Wily; Ayunda Rahmawati, Dayyinah (CV. AKIRA JAVA BULU, 2025)
This research aims to analyze the influence of digital literacy and education level on the political participation of the millennial generation in Bekasi City. The method used is a quantitative approach with regression analysis techniques using SmartPLS 4. The research sample of 35 respondents was selected through a simple random sampling technique. The test results show that digital literacy and education level have a positive and significant effect on the political participation of the millennial generation. The R Square value of 0.580 indicates that the two variables are able to explain the variation in political participation by 58%. This finding shows that the ability of the millennial generation to access, transmit, and use digital information, as well as a higher level of education, directly contribute to increasing their involvement in political activities. This study reinforces the importance of strengthening digital literacy and political education in encouraging democratic participation of the younger generation. The implication of this study is the need to develop a more structured digital literacy and political awareness education program to optimize the role of the millennial generation in political life in the digital era.